2013
DOI: 10.4187/respcare.02524
|View full text |Cite
|
Sign up to set email alerts
|

Value of Autofluorescence Imaging Videobronchoscopy in Detecting Lung Cancers and Precancerous Lesions: A Review

Abstract: SummaryBronchoscopy technology is a desirable method for detecting lung cancers arising in the central airways. Most early cancers and precancerous lesions are not visible on conventional white-light bronchoscopy (WLB). Autofluorescence bronchoscopy (AFB) is a newly developed technology that exploits the difference in autofluorescence intensity between normal and tumorous tissues to detect bronchial cancers and precancerous lesions. Several types of AFB systems have been used in clinical practice, and autofluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 67 publications
1
18
0
Order By: Relevance
“…Although it is not clear whether squamous metaplasia is the first stage of the pathogenetic process, followed by cartilage formation and ossification, or simply secondary to the chronicity of the condition, it remains the most common histopathological finding in TO patients (1,2). AFI is a newly advanced bronchoscopy system that can detect weak autofluorescence signals from the bronchial mucosa (6). This technique can identify abnormal mucosa with the aid of different colors; pathological mucosa appears magenta while normal bronchial mucosa appears green.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is not clear whether squamous metaplasia is the first stage of the pathogenetic process, followed by cartilage formation and ossification, or simply secondary to the chronicity of the condition, it remains the most common histopathological finding in TO patients (1,2). AFI is a newly advanced bronchoscopy system that can detect weak autofluorescence signals from the bronchial mucosa (6). This technique can identify abnormal mucosa with the aid of different colors; pathological mucosa appears magenta while normal bronchial mucosa appears green.…”
Section: Discussionmentioning
confidence: 99%
“…Bronchoscopy is the gold standard for TO diagnosis; however, it cannot satisfactorily assess subtle mucosal changes to determine the treatment response (5). Autofluorescence imaging bronchoscopy (AFI) is a recently introduced advanced endoscopic technology that can detect subtle mucosal changes with the aid of different colors (6). Here we report the AFI findings for a case involving a 42-yearold man with typical histopathological findings of TO.…”
Section: Introductionmentioning
confidence: 95%
“…Seven more studies evaluated the effectiveness of AFI: six studies found its sensitivity significantly higher than that of WLB, whereas the remaining study recorded the same value for AFI and WLB. Regarding the specificities of AFI compared to that of WLB, no univocal data were available (19) (Figure 1).…”
Section: A B Cmentioning
confidence: 99%
“…Autofluorescence is intensely produced by submucosal stroma, but epithelium, mucosa, and cancerous tissue emit very little fluorescence. Several mechanisms have been hypothesized to explain the different autofluorescence o f n o r m a l a n d c a n c e r o u s t i s s u e s : f o r e x a m p l e autofluorescence can change if the epithelial layer thickens, as in the presence of cancer, or if the concentrations of certain substances in the tissue, including fluorophores and nonfluorescent chromophores, change (51). Most endogenous fluorophores are associated with the tissue matrix, such as collagen and elastin, or are involved in cellular metabolic processes.…”
Section: Afbmentioning
confidence: 99%
“…AFB is an advanced technology that exploits the autofluorescent nature of bronchial mucosa to detect tiny and subtle superficial lesions (51). Several types of AFB systems have been designed, developed, and marketed, including the LIFE system (Xillix Technologies, Richmond, British Columbia, Canada), the D-Light system (Karl Storz, Tuttlingen, Germany), and the SAFE system (Pentax, Tokyo, Japan).…”
Section: Afbmentioning
confidence: 99%